Measurement of the degree of customer satisfaction cases: HABIB BOURGUIBA Hospital - Fayza Jallouli; Ismail Benzaala (Dirassat Journal Economic Issue, 2023)
Currently each hospital offers satisfaction surveys to its patients to observe how they evaluate the care services. Indeed, it is important for each hospital, whatever it is, to take an interest in the opinion of its patients about the care provided to them. These surveys allow hospitals to consider patient satisfaction as an indicator for judging the quality of care and services offered. In hospitals, patient satisfaction does not only correspond to the intervention or a simple consultation. On the contrary, it begins when the appointment is made, then continues when the patient arrives at the hospital and ends when he leaves. This study aims to measure the general level of patient satisfaction with all aspects of their care at Habib Bourguiba Hospital, to explain the length of stay in the hospital, as we can imagine that the longer patients stay in the care service, the greater the sources of dissatisfaction.We concluded that the most important thing for the patient is that he leaves the hospital “healed”.Currently each hospital offers satisfaction surveys to its patients to observe how they evaluate the care services. Indeed, it is important for each hospital, whatever it is, to take an interest in the opinion of its patients about the care provided to them. These surveys allow hospitals to consider patient satisfaction as an indicator for judging the quality of care and services offered. In hospitals, patient satisfaction does not only correspond to the intervention or a simple consultation. On the contrary, it begins when the appointment is made, then continues when the patient arrives at the hospital and ends when he leaves. This study aims to measure the general level of patient satisfaction with all aspects of their care at Habib Bourguiba Hospital, to explain the length of stay in the hospital, as we can imagine that the longer patients stay in the care service, the greater the sources of dissatisfaction.We concluded that the most important thing for the patient is that he leaves the hospital “healed”.